At Penpoint : African Literatures, Postcolonial Studies, and the Cold War - Popescu, Monica, 1973- (Theory in forms., 2020)
"AT PENPOINT aims to rewrite the story of postcolonial African literary and cultural production as one profoundly influenced by the Cold War. Monica Popescu shows how postcolonial studies of African literature have too often neglected the key institutional and aesthetic influence asserted by Soviet agents, and the resulting overlapping imperalisms African writers and creators worked within and contested during the second half of the twentieth century. Popescu's analysis attends to the myriad ways in which the tension between the United States and the USSR played out in the intellectual and aesthetic clashes among Third World intellectuals as well as on the battlefields of the proxy conflicts (specifically, the war in Angola) and experiments in African-style socialism that spread across the continent. Informed by several intellectual projects that have similarly brought postcolonial studies and the history of the Cold War together, Popescu traces a new cartography of cultural communication and meaning-making apart from a Western intellectual history and reinvigorates a leftist critique of imperialism too often occluded by postcolonial studies. Popescu uses her focus on the Cold War both to reassess familiar works from the era, such as Ayi Kwei Armah's The Beautyful Ones Are Not Yet Born as well as to shine light on previously un- or under-studied publications made newly relevant, including Lotus, the journal of the Afro-Asian Writers' Alliance. The book is divided into two parts; the first providing the historical and theoretical framing for the latter's analysis. Chapter 2 in part I introduces Popescu's theory of "aesthetic world systems" in order to frame an alternative aesthetic system set up by the Soviet Union to sway intellectuals disenchanted with Western thought to align their work to the norms and aesthetic values of a Soviet ideology. Popescu illustrates this tension evident in African literature by analyzing both how African writers debated the definitions and functions of realism and modernism within Cold War parameters as well as how the aesthetic prerogatives of both the US and the USSR rendered entire corpuses of Third World texts illegible and invisible. The book's second part takes up more specific works of literature, expanding African literary history by rearticulating connections between texts and contexts. In chapter 3 in part II, which considers Armah's novel among several others, Popescu examines how accounts of decolonization and neocolonialism also bear the traces of Cold War influence in their attitudes toward revolutionary social change and its aftermath Popescu closes with a rethinking of the shift from postcolonial studies to "world literatures," centering African writers' contributions to rethinking the very concept"--